Compositional and Microbiological Characteristics During Ripening of ¦etil Cheese, a Traditional Turkish Cheese - SENGUL, MUSTAFA; DEGIRMENCI, MEHTAP; ERKAYA, TUBA (Asian Journal of Chemistry, 2010)
The aim of this study was to investigate some physical and chemical (dry matter, fat, fat in dry matter, salt, salt in dry matter, acidity %, pH, protein, water-soluble protein, ripening degree, lipolysis and ash) and some microbiological (total aerobic mesophilic bacteria, coliform group bacteria, lactic acid bacteria, S. aureus, yeast and mould) properties during the repining time (1, 30, 60 and 90 days) of Çeçil cheese. Dry matter, fat, salt, pH, acidity, total protein, water-soluble protein, lipolysis (acid degree value) and ash values of samples analyzed were found as 48.68, 10.60, 8.08, 5.76, 0.27, 27.69, 2.69, 1.45, 10.02 %, respectively. In the samples, average of total aerobic mesophilic bacteria, lactic acid bacteria, yeast and moulds, coliform bacteria and Staphylococcus aureus were determined to be 6.65, 5.57, 3.54, 0.87 and 1.35 1og cfu/g, respectively. S. aureus and coliform bacteria were determined in days 1st and 30th of ripening. According to the results, while ripening time was of great importance (p < 0.01) on dry matter, salt, salt in dry matter, pH, lipolysis, lactic acid bacteria, coliform, total aerobic mesophilic bacteria and S. aureus, acidity %, water-soluble protein, fat, fat in dry matter, ripening degree, ash and yeast and mould were found insufficient (p > 0.05).